Development of Quality Culture and Work of Bapelkes Mataram - Fadjar, Mulyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Bapelkes NTB Province became Bapelkes Mataram as a UPT within the Ministry of Health based on the Minister of Health Decree No. 29 of 2021 concerning the Organization and Work Procedures of the Technical Implementation Unit for Health Training in the Ministry of Health. Bapelkes Mataram as one of the organizations under the Ministry of Health of the Republic of Indonesia in its readiness to carry out re-accreditation continues to evaluate the development of education and training services by implementing a quality culture and work of Bapelkes Mataram with benchmarks on the Professional - Innovative - Solid aspect which is abbreviated as PIS. Qualitative descriptive method which is a follow-up research as a form of evaluation of the application of quality and work culture. Using research instruments that were refined from previous studies. The results of this study provide an illustration of an increase of 19.33%. Input on the dissemination of survey results to triangulate data on the Solid (S) indicator component to get results that are the real situation. The diversity of organizational forms that will affect different cultures is a natural thing because of the different organizational environments. Several activities were carried out in an effort to establish and improve Professional Values (P) and Solid Values (S) with the “Raboan” meeting activity; make a work schedule for Manager On Duty (MOD) holidays and public holidays; appoint a technical implementing coordinator for the Bapelkes Mataram with a mentor. Continuous evaluation in an effort to achieve success in institutional re-accreditation will be achieved.